PELAKSANAAN PEMBAYARAN ROYALTI PADA LAGU YANG DIGUNAKAN OLEH RADIO DI PEKANBARU BERDASARKAN PERATURAN PEMERINTAH NOMOR 56 TAHUN 2021 TENTANG PENGELOLAHAN ROYALTI HAK CIPTA LAGU DAN MUSIK - Shofa Rizkina Pratiwi.A; Zulfikar Jayakusuma; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law Number 28 of 2014 concerning copyright, hereinafter referred to as theCopyright Law in Article 1 Paragraph 1, says that copyright is the copyright of thecreator that arises automatically based on the declarative principle after a work isrealized in a tangible form without reducing the complexity in accordance withthe provisions of the legislation. One of the intellectual property products includedin intellectual property rights is a song. The use of songs accompanied by materialbenefits, one of which is in radio media. As quoted from Government RegulationNumber 56 of 2021 Article 3 paragraph (1) that "everyone can make commercialuse of songs and or music in the form of commercial public services by payingroyalties to creators, copyright holders, and or rights owners." related throughLMKN. The purpose of writing this thesis namely; First, the implementation ofroyalty payments for songs used by radio in Pekanbaru city. Second, factors thatbecome obstacles in implementing royalty payments for songs used by radio inPekanbaru city.This type of research can be classified into the type of sociologicaljuridical research, examining the legal aspects by looking at the applicablelegislation and comparing it with the implementation obtained in the field. Thisresearch was conducted at the RRI and Gress FM radio companies, while thepopulation and sample were all parties related to the problems studied in thisstudy. Sources of data used are primary data and secondary data. Methods of datacollection in this study by interviews and literature study.From the results of the research problem, there are two main things thatcan be concluded. First, the implementation of royalty payments on both privateradio and state radio in Pekanbaru has a difference, where royalty payments byprivate radio in Pekanbaru do not carry out according to applicable regulations,while on radio The country, namely RRI radio, stated that the central RRI radiohad paid according to the procedures in force. Second, the factor that becomes anobstacle in the payment of royalties is that private radio does not benefit from theJOM Fakultas Hukum Universitas Riau Volume X No. 1 Januari – Juni 2023 Page 2songs that must be paid royalties and the second factor is due to a lack ofunderstanding of the rules governing the payment of royalties. Author'ssuggestion, First, LMKN must immediately create and use a Song and MusicInformation System and optimize its use to facilitate royalty management.Second, LMKs need to make improvements in collecting royalties, LMKNs needto socialize the Copyright Law, Content, and the rules contained in the Law inorder to increase understanding of the importance of paying royalties.Keywords: Payment-Royalty